The Status of Land Ownership Due To Marriage Between Indonesian Citizens And Foreign Citizens Is Reviewed According To Agrarian Law In Indonesia - Agustina, Yanti; zulkifli, Suhaila; Simanjuntak, Immanuel (Journal of Law, Politic and Humanities, 2025)
Marriage that occurs between Indonesian citizens and foreigners has consequences for joint property, especially for land ownership which is joint property in marriage. For marriages that are carried out without making an agreement on the separation of property, the land becomes the joint ownership of the husband and wife. This means that both of them who are bound by marriage become the owners of the land. According to the provisions of agrarian law, foreigners are not allowed to own land in Indonesia, so the presence of foreigners who participate as land owners causes problems with the ownership of land. Consequently in this case, it is necessary to conduct research on the status of land ownership due to marriage carried out by Indonesian citizens and foreigners reviewed according to agrarian law in Indonesia. The type of research used is normative juridically, namely analyzing laws to answer problems in research. As for the results of the research on the status of land ownership due to the marriage of Indonesian citizens and foreigners without a separation agreement on marital property, both must transfer or release the rights to the land for a maximum of 1 year because the land ownership requirements are no longer in accordance with the provisions of the law